Long-Term Outcome of Idiopathic Macrocephaly - J Gordon Millichap (Pediatric Neurology Briefs)
The neuroradiological, developmental, and psychological, long-term sequelae of 41 infants (30 boys, 11 girls) diagnosed with macrocephaly (an occipito-facial head circumference [OFC] >95th centile) at a family health service visit between 1985 and 1986 were studied at the Royal Alexandra Hospital for Children and other centers in Sydney, Australia.